(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Volatility modelling in Nigeria and sub-Sahara Africa lacks the use of non–Gaussian models for estimating stock market returns series; researchers have been focusing on the Gaussian process. To overcome this deficiency, we used non-Gaussian assumptions alongside normal assumptions. Our major focus here is to investigate the presence of leverage effect and volatility persistence in Nigeria Exchange non-Normal specifications. GARCH models and their asymmetric extensions viz. EGARCH, TGARCH and PGARCH were employed to conduct the analysis with each estimated in Normal, Student’s-t and Generalized error distributions. Student-t specification outperformed the other error distribution models. Important outcomes of the study include that the Exchange did not have an evidence of leverage effect; EGARCH, TGARCH and PGARCH models all showed empirical results contrary to the theoretical a priori signs of asymmetry. Secondary, there is high volatility persistence in the market, EGARCH model even indicated an explosive volatility persistence. We conclude that Nigeria Exchange is dominated by uninformed investors with a short-term investment strategy. Additionally, the market is very volatile and has the implication of weakening the investors’ confidence.